2022
DOI: 10.3389/fpls.2022.845794
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of growth and Cannabinoids content of hemp (Cannabis sativa) using arbuscular mycorrhizal fungi

Abstract: This study aimed to investigate the efficiency of arbuscular mycorrhizal fungi (AMF) to promote growth and cannabinoid yield of Cannabis sativa KKU05. A completely randomized design (CRD) was conducted with six replications for 60 days. Two different species of AMF, Rhizophagus prolifer PC2-2 and R. aggregatus BM-3 g3 were selected as inocula and compared with two non-mycorrhizal controls, one without synthetic fertilizer and one with synthetic NPK fertilizer. The unfertilized non-mycorrhizal plants had the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The underlying mechanism of enhanced synthesis of these bioactive compounds is currently unknown. In a study on Cannabis sativa [41], the increase in bioactive compounds was correlated with increases in phosphorus acquisition. However, in this study, mineral fertilizer plants showed the highest shoot concentration of N, P, and K, but this did not result in the highest concentrations of bioactive compounds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The underlying mechanism of enhanced synthesis of these bioactive compounds is currently unknown. In a study on Cannabis sativa [41], the increase in bioactive compounds was correlated with increases in phosphorus acquisition. However, in this study, mineral fertilizer plants showed the highest shoot concentration of N, P, and K, but this did not result in the highest concentrations of bioactive compounds.…”
Section: Discussionmentioning
confidence: 98%
“…Both nutritional and non-nutritional factors have therefore been proposed to explain the increased production of secondary metabolites in AMF-colonized plants [35]. Nutritional mechanisms refer to the improvement of the nutritional condition of the host [41][42][43]. Zhao et al [35] summarized current knowledge on potential non-nutritional mechanisms by stating that AMF colonization results in the activation of plant defense mechanisms with the production of phenolics and flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…( P. fluorescens, Pseudomonas protegens , and P. putida ), seem to be naturally present in hemp tissues and surrounding soil. In a study with arbuscular mycorrhizal fungi ( Rhizophagus prolifer and R. aggregatus ) Seemakram et al [ 62 ] found a significant influence on plant length, leaf surface area (cm 2 ) and root dry weight, but also increment of plant total cannabinoids content (CBD, CBDA, CBG, THC) with mycorrhizal fungi 60 days after sowing C. sativa (cultivar KKU05).…”
Section: Discussionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) could live in a mutualistic symbiosis with plant roots of the majority (> 80%) of terrestrial plant species ( Kalamulla et al, 2022 ; Seemakram et al, 2022 ). Sweet potato was easily colonized by mycorrhizal fungi ( O’Keefe and Sylvia, 1993 ; Minemba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the beneficial interaction of AMF with sweet potato is considered suitable for the cultivation of sweet potato. Typically, AMF develop extraradical mycelia that extend the depletion zone that develops around roots, and facilitate the acquisition of nutrients of low mobility ( Seemakram et al, 2022 ). Consistent with this phenomenon, a meta-analysis about the effects of AMF on plant growth and nutrient uptake reflected that AMF could increase plant nitrogen (N), phosphorus (P), and K uptake by 22.1, 36.3, and 18.5%, respectively ( Chandrasekaran, 2020 ).…”
Section: Introductionmentioning
confidence: 99%